EDC/NHS activation mechanism of polymethacrylic acid: anhydride versus NHS-ester1. Issue 86 (18th September 2015) - Yan, Qin; Zheng, Hong-Ning; Jiang, Chuan; Li, Kun; Xiao, Shou-Jun
<x xml:space="preserve">Abstract</x> Both stable intermediates of anhydride and NHS-ester were observed after EDC/NHS activation of PMAA, where NHS-ester waxes, while anhydride wanes complementarily with increasing fragmentation degree of PMAA blocks in PMAA-associated polymer blends.